MANAJEMEN DAKWAH TAMAN QURAN MULIA DALAM UPAYA MENINGKATKAN MINAT REMAJA MENJADI HAFIDZ DAN HAFIDZAH - Ahmad Harfan, Irfan; Karsih, Ucu (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2022)
Abstract : The purpose of this study is to describe and to determine the supporting and inhibiting factors of the management of the Da'wah Taman Quran Mulia in an effort to increase the interest of adolescents to become hafidz and hafidzah in Margasari Village, Luragung District, Kuningan Regency. This study uses a qualitative method with a case study approach. The data collection techniques were carried out through observation, in-depth interviews, and documentation study. The results of this study indicate that 1) In its planning, Taman Quran Mulia has implemented a hafidz Quran printing program that runs according to the expectations of the institution, including by holding meetings to prepare everything needed, determining the implementers, and determining all facilities in the implementation of the process of fostering students. in order to memorize Al-Quran 30 Juz. 2) Organizing the tasks given to the management or teaching staff is a task that is in accordance with their expertise and the work program provided is to provide the best facilities in fostering Quran memorizing students so that they have noble morals and practice ahlussunnah waljama'ah. 3) One of the management of the movement carried out by the leadership is to provide motivation and encouragement to the management or teaching staff so that they can work well in order to achieve the hafidz Quran printing program. 4) Supervision is carried out by the leadership, namely by observing all activities and duties of the management or teaching staff so that the achievement of the hafidz Quran printing program can be carried out properly and as expected. The supporting and inhibiting factors for the management of da'wah at Taman Quran Mulia are carried out through strategic planning methods to evaluate internal and external factors including: 1) The strength of Taman Quran Mulia has a strong vision, mission and has the potential for the quality of teaching staff and students and has adequate facilities and infrastructure. adequate. 2) The weakness that occurs is the limited human resources as administrators or teaching staff. 3) Opportunities Taman Quran Mulia has received recognition from the public as a non-formal institution that manages salaf, 4) The challenge for Taman Quran Mulia is the development and technological changes that make teenagers not interested in becoming hafidz Quran. Keywords: Da'wah Management, Youth Interests, Hafidz Hafidzah